2007
DOI: 10.1007/s00246-006-1450-9
|View full text |Cite
|
Sign up to set email alerts
|

Neurodevelopmental Outcomes Following Congenital Heart Surgery

Abstract: Advances in both surgical techniques and perioperative care have led to improved survival outcomes in infants and children undergoing surgery for complex congenital heart disease. An awareness is emerging that early and late neurological morbidities complicate the outcome of these operations. Adverse neurological outcomes after neonatal and infant cardiac surgery are related to both fixed and modifiable mechanisms. Fixed factors include many variables specific to the individual patient, including genetic predi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
99
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(107 citation statements)
references
References 80 publications
7
99
0
1
Order By: Relevance
“…Our findings extend the knowledge of long-term neurological impairment and mental health functional morbidities in the population with CHD. Although previous studies have reported elevated risks of adverse neurodevelopmental outcomes among individuals with CHD, including increased occurrence of depression, autism, and epilepsy compared with the general population, [6][7][8]19,[32][33][34][35] our study examined an older adult population to determine the later-life consequences of this neurological outcome. Although the underlying pathophysiological mechanisms are not completely understood, the potential etiologic factors appear multifactorial and consistent with previous findings within the neurodevelopmental scientific literature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings extend the knowledge of long-term neurological impairment and mental health functional morbidities in the population with CHD. Although previous studies have reported elevated risks of adverse neurodevelopmental outcomes among individuals with CHD, including increased occurrence of depression, autism, and epilepsy compared with the general population, [6][7][8]19,[32][33][34][35] our study examined an older adult population to determine the later-life consequences of this neurological outcome. Although the underlying pathophysiological mechanisms are not completely understood, the potential etiologic factors appear multifactorial and consistent with previous findings within the neurodevelopmental scientific literature.…”
Section: Discussionmentioning
confidence: 99%
“…4,5 Neurodevelopmental deficits among infants and children with CHD are well described. [6][7][8] However, research on long-term neurological outcomes in adults with CHD is more limited. Dementia is among the most important late-life neurological diseases in the general population.…”
mentioning
confidence: 99%
“…Ballweg et al (19) have shown that fetuses with CHD exhibits poor neurologic development primary caused by cardiac surgical interventions. However, there is evidence that that brain injuries in CHD patients may be detected at birth and may be caused by chronic cerebral hypoxia due to direct delivery of deoxygenated blood or by intracardiac mixing of oxygenated and deoxygenated blood during the fetal period (20).…”
Section: Editorialmentioning
confidence: 99%
“…Numerous studies have shown that cardiopulmonary bypass (CPB) and deep hypothermic circulatory arrest (DHCA) are responsible for long-term sequelae such as neurological, developmental, motor and behavioral deficits [1][2][3]. The high occurrence of motor abnormalities is a major concern because these can affect between 20% and 60% of patients [2,3].…”
Section: Introductionmentioning
confidence: 99%